The Effects of Using an Environmentally Based Inquiry Learning Model on SMA Students' Cognitive Abilities and Concern for the Environment on Air Pollution Concept - Fitriyani, Nera; Ratnasari, Jujun; Munadiah, Hilda (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Sukabumi, 2022)
Background: In class X at SMA Negeri 3 Sukabumi City, research has been done on how integrating an environmental-based inquiry learning approach affects students' cognitive capacities and environmental concern around the notion of air pollution. The purpose of this study is to: (1) ascertain how the environmental-based inquiry learning paradigm affects students' environmental consciousness and cognitive capacities. (2) to ascertain how the environmental-based inquiry learning paradigm was received by the students. Research of this kind is quasi-experimental. All SMA Negeri 3 Sukabumi City class X pupils made up the study's population. Two sixty-six-student classes were selected as samples, one of which served as the experimental class and the other as the control class. Class X IPA has as many as 33 students as the experimental class using the environment-based inquiry learning model, while class X IPA has as many as 33 students as the control class using the STAD-type cooperative learning model with a nonrandom sampling technique, namely, purposive sampling. Methods: The analysis technique used is a non-parametric test, namely the Wilcoxon test for analyzing pretest and posttest data, and a parametric test, namely the t test for analyzing student concern for the environment questionnaire data. Results: The results of the study with α = 0.05% and 95% confidence level showed: (1) the environment-based inquiry learning model does not affect students' cognitive abilities with Whitung =188.5 > Wtabel (0.05)(33) =170. (2) The environment-based inquiry learning model does not affect students' concern for the environment, with tcount = 0.72 < ttable (0.975)(64) =1.9987. (3) Student responses in the experimental class showed a positive response to the environment-based inquiry model. Based on the research as a whole, it can be concluded that the environment-based inquiry learning model does not affect students' cognitive abilities or students' concern for the environment, but shows a positive response to the environment-based inquiry learning model applied to the experimental class. Keywords : Environment-based inquiry learning model; cognitive abilities; students' concern for the environment.